The Influence of Employee Performance on Service Quality - Sukmara, Sukmara; Sumiati, Nia; Barokah, Rezky Barokah Afiahtul (Almana : Jurnal Manajemen dan Bisnis, 2024)
The background for conducting this research is to provide additional information and input for the Bandung City Regional Secretariat and the Regional Government in general as a basis for input for decision-making in the context of evaluation and improvement. This study aims to determine whether employee performance affects the quality of service at the General Section of the Bandung City Regional Secretariat. The research methods used are descriptive and verification methods. The population in this study were employees at the General Section of the Regional Secretariat of the City of Bandung, totaling 60 people. The sampling technique is non-probability sampling using a saturated sample, so the number of samples is 60 employees in the General Section of the Regional Secretariat of the City of Bandung. The data collection technique used in this study was through a research questionnaire with a Likert scale type. Data analysis used in this research is simple linear regression analysis using SPSS software. The results of the study show that employee performance influences the quality of service at the General Section of the Bandung City Regional Secretariat. The magnitude of the influence of employee performance on service quality is 37.4%.